B-Cell Depletion Promotes Aortic Infiltration of Immunosuppressive Cells and Is Protective of Experimental Aortic Aneurysm. Issue 11 (November 2016) - Schaheen, Basil; Downs, Emily A.; Serbulea, Vlad; Almenara, Camila C.P.; Spinosa, Michael; Su, Gang; Zhao, Yunge; Srikakulapu, Prasad; Butts, Cherié; McNamara, Coleen A.; Leitinger, Norbert; Upchurch, Gilbert R.; et al.
Abstract : Objective—: B-cell depletion therapy is widely used for treatment of cancers and autoimmune diseases. B cells are abundant in abdominal aortic aneurysms (AAA); however, it is unknown whether B-cell depletion therapy affects AAA growth. Using experimental models of murine AAA, we aim to examine the effect of B-cell depletion on AAA formation. Approach and Results—: Wild-type or apolipoprotein E–knockout mice were treated with mouse monoclonal anti-CD20 or control antibodies and subjected to an elastase perfusion or angiotensin II infusion model to induce AAA, respectively. Anti-CD20 antibody treatment significantly depleted B1 and B2 cells, and strikingly suppressed AAA growth in both models. B-cell depletion resulted in lower circulating IgM levels, but did not affect the levels of IgG or cytokine/chemokine levels. Although the total number of leukocyte remained unchanged in elastase-perfused aortas after anti-CD20 antibody treatment, the number of B-cell subtypes was significantly lower. Interestingly, plasmacytoid dendritic cells expressing the immunomodulatory enzyme indole 2, 3-dioxygenase were detected in the aortas of B-cell–depleted mice. In accordance with an increase in indole 2, 3-dioxygenase+ plasmacytoid dendritic cells, the number of regulatory T cells was higher, whereas the expression of proinflammatory genes was lower in aortas of B-cell–depleted mice. In a coculture model, the presence of B cells significantly lowered the number of indole 2, 3-dioxygenase+ plasmacytoid dendritic cells without affecting total plasmacytoid dendritic cell number. Conclusions—: The present results demonstrate that B-cell depletion protects mice from experimental AAA formation and promotes emergence of an immunosuppressive environment in aorta. Abstract : Supplemental Digital Content is available in the text.